Patient‐reported outcomes after 10‐year follow‐up of intensive, multifactorial treatment in individuals with screen‐detected type 2 diabetes: the ADDITION‐Europe trial. Issue 9 (8th August 2020) - Dalsgaard, E.‐M.; Sandbæk, A.; Griffin, S. J.; Rutten, G. E. H. M.; Khunti, K.; Davies, M. J.; Irving, G. J.; Vos, R. C.; Webb, D. R.; Wareham, N. J.; Witte, D. R.
Abstract: Aims: To present the longer‐term impact of multifactorial treatment of type 2 diabetes on self‐reported health status, diabetes‐specific quality of life, and diabetes treatment satisfaction at 10‐year follow up of the ADDITION‐Europe trial. Methods: The ADDITION‐Europe trial enrolled 3057 individuals with screen‐detected type 2 diabetes from four centres [Denmark, the UK (Cambridge and Leicester) and the Netherlands], between 2001 and 2006. Participants were randomized at general practice level to intensive treatment or to routine care . The trial ended in 2009 and a 10‐year follow‐up was performed at the end of 2014. We measured self‐reported health status (36‐item Short‐Form Health Survey and EQ‐5D), diabetes‐specific quality of life (Audit of Diabetes‐Dependent Quality of Life questionnaire), and diabetes treatment satisfaction (Diabetes Treatment Satisfaction Questionnaire) at different time points during the study period. A mixed‐effects model was applied to estimate the effect of intensive treatment (intention‐to‐treat analyses) on patient‐reported outcome measures for each centre. Centre‐specific estimates were pooled using a fixed effects meta‐analysis. Results: There was no difference in patient‐reported outcome measures between the routine care and intensive treatment arms in this 10‐year follow‐up study [EQ‐5D: –0.01 (95% CI –0.03, 0.01); Physical Composite Score (36‐item Short‐Form Health Survey): –0.27 (95% CI –1.11, 0.57), Audit of Diabetes‐Dependent Quality of Life questionnaire: –0.01 (95% CI –0.11, 0.10); and Diabetes Treatment Satisfaction Questionnaire: –0.20 (95% CI –0.70, 0.29)]. Conclusions: Intensive, multifactorial treatment of individuals with screen‐detected type 2 diabetes did not affect self‐reported health status, diabetes‐specific quality of life, or diabetes treatment satisfaction at 10‐year follow‐up compared to routine care. What's new?: The burden of diabetes and its treatment may cause psychosocial stress. Good metabolic control improves psychosocial well‐being. Identifying people early in the disease course through screening and introducing long‐term intensive treatment does not cause psychosocial harm. Clinicians and public health systems implementing early detection and intensive treatment protocols for type 2 diabetes do not need to worry that these may have a long‐term adverse impact on peoples' psychosocial well‐being.